1995
DOI: 10.1097/00001888-199506000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Validity of three clinical performance assessments of internal medicine clerks

Abstract: There was convergent validity and some evidence of divergent validity with a significant method effect. The findings were similar for correlations corrected for attenuation. Four conclusions were reached: (1) the reliability of the OSCE must be improved, (2) the CEF ratings must be redesigned to further discriminate among the specific traits assessed, (3) additional methods to assess personal characteristics must be instituted, and (4) several assessment methods should be used to evaluate individual student pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 0 publications
7
36
0
2
Order By: Relevance
“…In other words, a student's ability to perform during the process of sitting a written work versus in an OSCE station in front of an examiner on another human being could, by itself, provide the rationale for the low correlations seen between these two variables. Interestingly, the correlations between anatomy OSCE and written examinations (which were predominantly MCQs) from this study compare closely with the published literature on correlations between OSCE marks in general and MCQs in other subjects (Hull et al, 1995;Wass et al, 2001;Auewarakul et al, 2005). The ranges of correlations between these three different studies were 0.28-0.48, which are in a similar range and consistent with the findings obtained in this study.…”
Section: Anatomy Osce and Anatomy Written Examination Performance Corsupporting
confidence: 91%
“…In other words, a student's ability to perform during the process of sitting a written work versus in an OSCE station in front of an examiner on another human being could, by itself, provide the rationale for the low correlations seen between these two variables. Interestingly, the correlations between anatomy OSCE and written examinations (which were predominantly MCQs) from this study compare closely with the published literature on correlations between OSCE marks in general and MCQs in other subjects (Hull et al, 1995;Wass et al, 2001;Auewarakul et al, 2005). The ranges of correlations between these three different studies were 0.28-0.48, which are in a similar range and consistent with the findings obtained in this study.…”
Section: Anatomy Osce and Anatomy Written Examination Performance Corsupporting
confidence: 91%
“…[5][6][7][8] Similar correlations are found in the adult literature. 18,19 In their review of tests using standardized patients, van der Vleuten and Swanson 16 statistically correct for measurement error by making the tests perfectly reliable. In all cases the true correlations between other measures of competence, both written tests and clinical evaluations, increased greatly over the observed correlations, with the majority of coefficients greater than 0.40.…”
Section: Validity Of the Oscementioning
confidence: 99%
“…The reliability of similar types of assessment processes have been variable, although many have claimed adequate reliability (Keck and Arnold 1979;Kwolek et al 1997;Magzoub et al 1998;Kreiter et al 1998;Nasca et al 2002;Durning et al 2005;Beckman et al 2006;Cohen et al 2009;Kreiter et al 1998), others have been either equivocal (Cowles and Kubany 1959;Hull et al 1995;Schwanz et al 1995;Williams et al 2004), or found the reliability not acceptable (Levine and McGuire 1971;Davis et al 1986;Thompson et al 1990;Metheny 1991;Ryan et al 1996;Pulito et al 2007;Searle 2008). A common problem with many of the studies claiming reliability for this form of competency assessment has been the inappropriate use of the alpha coefficient for nested and/or unbalanced designs which appears to be common for workplace-based assessments (Keck and Arnold 1979;Magzoub et al 1998;Nasca et al 2002;Durning et al 2005;Cohen et al 2009).…”
Section: Comparison To Other Studiesmentioning
confidence: 99%